An empirical assessment of individual-level determinants of social capital in Central European countries - José Mondéjar Jiménez; Juan-Antonio Mondéjar-Jiménez; María-Leticia Meseguer-Santamaría; Manuel Vargas Vargas (Journal for East European Management Studies, 2011)
This paper carries out an empirical assessment of the influence relationship between personal attitudes and several measures of social capital in some Central European Countries (CEC). Using the World Values Survey dataset, the model measures three main social capital dimensions (institutional trust, social participation and political participation) and four personal attitudes factors (collectiveness, education, gender differences and work). The analysis provides relevant information about personal determinant of social capital, in its political approach and, also, about the key role of institutional trust for civic engagement in social and political participation. – – Dieser Artikel führt eine empirische Untersuchung über den Einfluss der Beziehung zwischen persönlichen Eigenschaften und verschiedenen Maßzahlen von Sozialkapital in mehreren zentraleuropäischen Ländern durch. Das Modell zieht den Datensatz des World Values Survey heran und misst drei Hauptdimensionen von Sozialkapital (Vertrauen in Institutionen, gesellschaftliche und politische Teilhabe). Außerdem bestimmt es noch vier Faktoren für persönliche Eigenschaften (Kollektivität, Erziehung, Geschlechterunterschiede und Arbeit) durch synthetische Indikatoren. Die Analyse liefert, in ihrer politischen Herangehensweise, relevante Informationen über die Bestimmungsgröße von Sozialkapital und über die Schlüsselrolle von Vertrauen in Institutionen für bürgerliches Engagement bei gesellschaftlicher und politischer Teilhabe.
Keywords: 650; Central European countries; civic engagement; PLS models; social capital; trust